Power play - Pearson, Ridley (Pearson, Ridley. Kingdom keepers, 2022)
The Kingdom Keepers learn that the Overtakers are planning to rescue their two captured leaders. Suddenly Charlene begins acting strangely and is caught sneaking into Epcot as a hologram. Finn and Philby gather the Keepers and spring into action as the Overtakers grow larger and begin recruiting kids to execute their sinister plans.